Sexually transmitted infections among patients attending the General Practice Clinic, Wesley Guild Hospital, Ilesa, Nigeria - S.S. Olakolu; E.A. Abioye Kuteyi; O.O. Oyegbade (South African Family Practice)
Background: Sexually transmitted infections (STIs) are among the most common infectious diseases in the world today. There are few reliable statistics on the true prevalence of STIs in developing countries, especially in the general practice setting, hence the need to determine the prevalence in each locality. With the scourge and pandemicity of human immunodeficiency virus (HIV) and the fact that STIs are recognised as independent risk factors for its transmission, determining the risk profiles for STIs has become paramount. The aim of this study was to describe the pattern of STIs among patients attending a Nigerian general practice (GP) clinic.